2015
DOI: 10.1016/j.ygyno.2015.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Glucose promotes cell proliferation, glucose uptake and invasion in endometrial cancer cells via AMPK/mTOR/S6 and MAPK signaling

Abstract: Objectives Obesity and diabetes are well-known risk factors for the development of endometrial cancer. A high rate of aerobic glycolysis represents a key mechanism by which endometrial cancer cells consume glucose as its primary energy source. The up-regulated glycolytic pathway is a common therapeutic target whose inhibition has implications for anti-tumor activity in cancer cells. This study aimed to investigate the effect of various concentrations of glucose on cell proliferation in endometrial cancer. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 40 publications
4
109
0
Order By: Relevance
“…This is a major energy source for the growth of UECC [40]. In conclusion, based on our study and other research, it can be concluded that HG increases the expression of GLUT4 via upregulating ER.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 72%
“…This is a major energy source for the growth of UECC [40]. In conclusion, based on our study and other research, it can be concluded that HG increases the expression of GLUT4 via upregulating ER.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 72%
“…[24] High glucose increases glucose uptake and glycolytic activity, and stimulates cell proliferation through modulating the MAPK pathway. [25] Apart from PI3K/Akt pathway, MAPK pathway should be suspected to activate and greatly implicate in PTC development. [26] Even if there has been no research to investigate the MAPK pathway in PTC patients with T2DM, it is notable that MAPK pathway may be involved in diabetes affecting PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Han et al reported an increased ability of adhesion and invasion in two EC cell lines, suggesting that targeting glucose metabolism may be a promising therapeutic strategy for the treatment of EC (33).…”
Section: Discussionmentioning
confidence: 99%